Fetal Hemoglobin Levels as Indicator of Frequency and Duration of Blood Donation (International Journal of Scientific Research and Management (IJSRM), 2021)
Hemoglobin F is normal hemoglobin seen in minute amount in adults. Increase in its level in adults is an indication of erythropoietic stress, which in most cases is linked to hemoglobinopathy. This study was undertaken to assess if physiological erythropoietic stress as seen in commercial blood donation, can increase it and thus be used as an indicator of frequency and duration of blood donation. The study involved 152 subjects including 88 commercial blood donors and 64 controls. Hemoglobin F was expressed as percentage concentration of the total hemoglobin. Results showed that hemoglobin F significantly increased in commercial blood donors when compared with the controls. There was also strong positive correlation between hemoglobin F level and age of the donors which was not the case with the controls. The results indicate that hemoglobin F level can be used as an indicator of the frequency and duration of blood donation. Though blood donation has some health benefits, the disadvantages of frequent donation outweigh these benefits and should be discouraged.